Antimicrobial susceptibility pattern of blood culture isolates from patients with suspected neonatal sepsis in a tertiary care hospital in Pakistan - T Ghafoor; A Hussanain; MM Qureshi; T Mehmood; L Ali (Sri Lankan Journal of Infectious Diseases, 2020)
Introduction: Neonatal septicemia is one of the commonest reasons for neonatal morbidity and mortality in developing countries. Knowledge of microbial flora and their susceptibility will help paediatricians decide on empirical treatment of neonatal sepsis. Objective: To determine the antimicrobial susceptibility of blood culture isolates from patients with suspected neonatal sepsis in a tertiary care hospital in Pakistan.   Study design: A laboratory based prospective study was carried out in the Department of Pathology, Combined Military Hospital, Sialkot, from March 2017 to February 2019. Methods: Blood culture and sensitivity testing was carried out on patients admitted for suspected neonatal sepsis from March 2017 to February 2019. Antimicrobial susceptibility testing of blood culture isolates was carried out by disk diffusion method using the Clinical Laboratory Standard Institute (CLSI) guidelines. Results: During the study period, 345 blood cultures from 345 neonates (age range 1 day-28 days; mean age 13 days) were received by the laboratory, of which76 were culture positive. Gram negative bacilli were isolated from 44 cultures and Gram positive cocci from the remaining 32. Staphylococcus aureus was the commonest isolate (n=28) followed by Escherichia coli (n=10), Klebsiella pneumoniae (n=9) and Acinetobacter spp. (n=8). Methicillin resistant S. aureus (MRSA) constituted (n=19) 25% of culture positive isolates. Pseudomonas aeruginosa was isolated from six patients. Serratia spp., Enterobacter spp. and Enterococcus spp. from four patients each and Proteus spp. isolated from three patients. Linezolid was the most effective antimicrobial against the isolated Gram positive cocci, with 93.7% sensitivity demonstrated by MRSA, methicillin sensitive S. aureus and enterococcus spp. followed by sensitivity to clindamycin at 92.8%. Among Gram negative isolates, more than 80% of E. coli, K. pneumonia and Acinetobacter spp. were multidrug resistant.  Susceptibility to polymyxin-B and tigecycline was shown by 88% and 71% of these isolates. Conclusion: A high degree of antibiotic resistance was observed in both Gram positive and Gram negative isolates which reflects a dire need for culture facilities and antimicrobial susceptibility testing in hospitals in Pakistan. No group B β hemolytic streptococci were isolated, most likely due to predominantly late onset neonatal sepsis in this cohort.